2013
DOI: 10.1089/met.2012.0153
|View full text |Cite
|
Sign up to set email alerts
|

Which Liver Enzymes Are Better Indicators of Metabolic Syndrome in Adolescents: The Fifth Korea National Health and Nutrition Examination Survey, 2010

Abstract: ALT, AST/ALT, and GGT were found to be associated with clustering of metabolic syndrome components, and the relationships appear to be sex- and weight group-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 31 publications
(55 reference statements)
2
39
1
2
Order By: Relevance
“…We found that high BMI and dyslipidemia were factors associated with NAFLD in the hemodialysis patients, while high BMI, high ALT, and low LSM were factors associated with NAFLD in the control group patients. Previous studies have shown that ALT was found to be associated with the clustering of metabolic syndrome components [29,30]. The clinical factors associated with NAFLD in both the hemodialysis and control group patients in this study were compatible with the aforementioned AASLD guidelines [24].…”
Section: Discussionsupporting
confidence: 82%
“…We found that high BMI and dyslipidemia were factors associated with NAFLD in the hemodialysis patients, while high BMI, high ALT, and low LSM were factors associated with NAFLD in the control group patients. Previous studies have shown that ALT was found to be associated with the clustering of metabolic syndrome components [29,30]. The clinical factors associated with NAFLD in both the hemodialysis and control group patients in this study were compatible with the aforementioned AASLD guidelines [24].…”
Section: Discussionsupporting
confidence: 82%
“…Despite strong evidence about the association between the AST-to-ALT ratio and obesity-related metabolic disorders, there have been little data from prospective studies based on the incremental predictive value of the serum AST-to-ALT ratio for the onset of metabolic syndrome [10, 23]. In our study, an increasing AST-to-ALT ratio was correlated with a consistent reduction in the onset of metabolic syndrome and its components.…”
Section: Discussioncontrasting
confidence: 49%
“…An increased AST-to-ALT ratio is strongly suggestive of alcoholic liver disease, whereas a reduced ratio specifies non-alcoholic steatohepatitis [9]. Recent studies have reported that an increased AST-to-ALT ratio is inversely associated with the future development of metabolic syndrome [10, 11]. However, the clinical utility and ability of the AST-to-ALT ratio in predicting metabolic syndrome and its individual components is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, elevated liver enzymes were associated with MS. ALT and the AST-to-ALT ratio were associated with clustering of MS components in Korean adolescents [19]. Serum ALT levels were correlated with the component of MS in Korean postmenopausal women [20].…”
Section: Introductionmentioning
confidence: 99%